2021
DOI: 10.1155/2021/6622245
|View full text |Cite
|
Sign up to set email alerts
|

The Beneficial Impact of the Black Chokeberry Extract against the Oxidative Stress in the Sublingual Salivary Gland of Rats Intoxicated with Cadmium

Abstract: Cadmium (Cd) is one of the most harmful xenobiotics to which humans are exposed, mainly by the oral route, throughout life. Preventive strategies are searched as low intoxication with this element, among others due to its prooxidative properties, can be deleterious to health and the exposure to it is continuously increasing. Recently, interest has been paid to plant raw materials with a high antioxidative potential to oppose the prooxidative properties of cadmium, such as black chokeberry (Aronia melanocarpa L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 53 publications
2
25
0
Order By: Relevance
“…AL is a plant flavonoid and quercetin derivative with biological activity. Flavonoids are naturally occurring plant polyphenols, which are richly present in large quantities in fruits and vegetables . Flavonoids have many beneficial effects that are attributable to their significant antioxidant activity, antiresorptive effects, and scavenging of free radicals .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AL is a plant flavonoid and quercetin derivative with biological activity. Flavonoids are naturally occurring plant polyphenols, which are richly present in large quantities in fruits and vegetables . Flavonoids have many beneficial effects that are attributable to their significant antioxidant activity, antiresorptive effects, and scavenging of free radicals .…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids are naturally occurring plant polyphenols, which are richly present in large quantities in fruits and vegetables. 32 Flavonoids have many beneficial effects that are attributable to their significant antioxidant activity, antiresorptive effects, and scavenging of free radicals. 33 Most flavonoids have osteoblast-promoting and osteoclast-inhibiting effects.…”
Section: Discussionmentioning
confidence: 99%
“…Pb administration, in doses of 50 mg/kg in male rats, confirmed the oxidative stress changes while the only morphological difference between glands was that of parenchymal atrophy in the SMG versus increased ductal areas in the PG [23]. Cadmium (Cd), found in cigarette smoke, could induce damage to different tissues, including salivary glands, by its oxidative properties [2,26,27]. There are no histopathological evaluations regarding cadmium's effect on salivary gland tissues but biochemical evaluations have shown that Cd could induce oxidative stress with minor differences between studies, depending on the doses and periods of administration.…”
Section: Oxidative Stress Changes In the Salivary Glands Induced By H...mentioning
confidence: 99%
“…6 articles on the effect of chemotherapy drugs on salivary glands [5,12,15,16,18,19]; • 4 articles on the effect of ethanol on salivary glands [6,7,9,20]; • 9 articles on the effects of heavy metals on salivary glands [2,11,[21][22][23][24][25][26][27]; • 3 articles on the effect of fluoride on salivary gland [4,10,28]; • 4 articles on the effect of other substances, such as atrazine [29], high protein diet [8], hyperoxia [30], and sodium nitrite [31];…”
mentioning
confidence: 99%
“…These methods should be easily accessible and uncomplicated [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Foods containing significant amounts of antioxidant components can be used in the daily diet to prevent the dangerous effects of toxic metals on the human body [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Tea deserves particular attention.…”
Section: Introductionmentioning
confidence: 99%